2011
DOI: 10.1063/1.3592562
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructures in a binary mixture confined in slit-like pores with walls decorated with tethered polymer brushes in the form of stripes: Dissipative particle dynamics study

Abstract: Using dissipative particle dynamics, we investigate the behavior of a binary mixture, exhibiting demixing in a bulk phase, confined in slit-like pores with walls modified by the stripes of tethered brush of chains. Our main interest is to determine possible morphologies that can be formed inside the pore, depending on the geometrical parameters characterizing the system (the size of the pore and the width of the stripes). In order to describe the observed morphologies we calculate several characteristics, as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 86 publications
2
34
0
Order By: Relevance
“…Therefore, the total number of main and contraflow chains is the same. All beads are assumed to be of the same type, which is reflected in the fact that the parameter figure 1), impenetrable for the beads on both sides by applying the reflection algorithm described in detail in reference [39]. The same reflection algorithm is used at the external walls (solid lines in the same figure) but, alternatively, the periodic boundary conditions can be used in Z direction, similarly to the original reverse flow setup [56][57][58].…”
Section: -2mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the total number of main and contraflow chains is the same. All beads are assumed to be of the same type, which is reflected in the fact that the parameter figure 1), impenetrable for the beads on both sides by applying the reflection algorithm described in detail in reference [39]. The same reflection algorithm is used at the external walls (solid lines in the same figure) but, alternatively, the periodic boundary conditions can be used in Z direction, similarly to the original reverse flow setup [56][57][58].…”
Section: -2mentioning
confidence: 99%
“…Covering the surface by a polymer brush may introduce a pronounced reduction of friction, which lowers the pressure difference required to maintain the flow through a nanochannel [31]. Flow in polymer brushes has been the subject of numerous simulational studies in recent years [32][33][34][35][36][37][38].Recently, the equilibrium properties of binary mixture confined in a slit-like pore decorated with polymer brush stripes were studied by means of dissipative particle dynamics (DPD) [39,40]. It was found that, depending on the geometrical parameters characterizing the system (the size of the pore and the width of the stripes), several different structures (or morphologies) inside the pore can be formed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(see, e.g. [13][14][15][16]). With respect to the aggregation of the polyphilic star molecules, there are a number of studies of polymerosomes [17], ABC star block copolymers [18][19][20], as well as related systems, e.g., a mixture of diblock and homopolymers [21].…”
Section: Introductionmentioning
confidence: 99%
“…In certain aspects, similar ideas have been implemented by Sokołowski in the already developed very recent projects. In particular, Sokołowski together with Jaroslav Ilnytskyi and Taras Patsahan (Institute for Condensed Matter Physics of the National Academy of Science of Ukraine) were exploring the formation of structural patterns of mesoscopic objects within the framework of coarse-grained modelling under confinement [48,49] by using dissipative particle dynamics computer simulations. On the other hand, his interest in the elucidation of the role of orientational degrees of freedom in various properties of the homogeneous and inhomogeneous systems gave recent fruits in the density functional and computer simulation studies of the behavior of Janus fluids [50][51][52], and of nowadays fancy, patchy colloids [53].…”
mentioning
confidence: 99%